Assessment of Oral Hygiene Habits Among Dental and Other Faculty Students of University of Georgia - Ivanishvili, Rusudan; Alyari, Melika (Caucasus Journal of Health Sciences and Public Health, 2020)
The main purpose of oral care is the maintenance of a functional and comfortable oral cavity to improve self-esteem and reduce bacterial activity in the mouth and the risk of both local and systemic infection. It is widely accepted that oral health plays an important role in overall health. Precise knowledge of oral hygiene habits is very important. aim of this study was to assess and compare knowledge of oral hygiene skills among of dental and other faculties undergraduate students of university of Georgia.